Liburan Murah Meriah di Bali: 100 Tempat Menginap Bujet Rp. 150 Ribuan di Denpasar, Kuta, Ubud, Sanur, Pantai Lovina, Candidasa - Gagas Ulung (Jakarta:PT Gramedia Pustaka Utama, 2009)
Koleksi Referensi (Tidak Dipinjamkan)